Legal Evaluation Strategy to Bridging the Regulatory Gap in Facing Technological Developments and Globalization in Indonesia - Arbani, Tri Suhendra; Putri, Aulia Hasanah (Badan Pembinaan Hukum Nasional, 2024)
High-quality legal products are essential in ensuring legal certainty and enhancing public compliance. However, many regulations are found to be irrelevant and unresponsive to social, economic, and technological changes, reducing their effectiveness. This study aims to analyze the role of legal evaluation in improving the quality of legal products and compliance through the lens of responsive law theory. The research employs a conceptual approach with prescriptive legal analysis. The findings reveal that periodic legal evaluations can identify regulatory weaknesses, adapt laws to societal changes, and strengthen regulatory legitimacy. The study concludes that legal evaluation is a critical instrument in achieving responsive and relevant laws. It recommends strengthening systematic legal evaluation mechanisms, involving public participation, and aligning regulations with societal dynamics. This approach is vital for fostering public trust in the law and ensuring its social function.